SOSIALISASI PENTINGNYA PENGELOLAAN KEUANGAN KELUARGA DAN PEMBUATAN ANGGARAN YANG IDEAL DI RW 08 SUNTER AGUNG JAKARTA UTARA - Arivia Ananda; Koerniawan Hidajat (LPPM Universitas Bina Bangsa, 2024)
Managing family finances is an important aspect in achieving prosperity and financial stability in a household. The socialization activity carried out at RW 08 Sunter Agung, North Jakarta aims to increase understanding and skills in financial management and creating an ideal budget. The method of implementing this activity includes presenting material and interactive training to housewives who are PKK members, with a focus on active participation in the learning process. Evaluation of this activity showed that around 80% of participants were able to answer the quizzes, indicating the effectiveness of the delivery of the material. Discussions and interactions between participants and presenters also occur actively, creating a dynamic learning environment. The material presented includes the importance of managing family finances, financial planning, budgeting, as well as practical steps in planning and managing household finances. It is hoped that this activity can make a positive contribution in increasing financial literacy and community welfare at the local level, as well as encouraging the implementation of effective financial management practices in everyday life